2017
DOI: 10.1515/intag-2016-0053
|View full text |Cite
|
Sign up to set email alerts
|

Degradation rates of alachlor, atrazine and bentazone in the profiles of Polish Luvisols

Abstract: A b s t r a c t. The degradation rates of three herbicides (alachlor, atrazine, and bentazone) were examined according to OECD Guideline 307 in three profiles of grey-brown podzolic soil (Luvisol) in a laboratory experiment. The aim of the experiment was to determine herbicide degradation parameters and their relationships with soil properties. Degradation processes were effectively described by a first-order model. However, in some cases, the best results were produced by bi-phasic kinetics (hockey-stick and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The applied value was also the median value reported in the field studies by the EU dossier [ 8 ]. The experimental DDF values of 1:0.42:0.11 for Polish soils [ 25 ] were also applied. Our previous studies [ 25 , 29 , 30 ] demonstrated that DDF values for Polish soils, especially AR and LV profiles, are lower than default FOCUS values.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The applied value was also the median value reported in the field studies by the EU dossier [ 8 ]. The experimental DDF values of 1:0.42:0.11 for Polish soils [ 25 ] were also applied. Our previous studies [ 25 , 29 , 30 ] demonstrated that DDF values for Polish soils, especially AR and LV profiles, are lower than default FOCUS values.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental DDF values of 1:0.42:0.11 for Polish soils [ 25 ] were also applied. Our previous studies [ 25 , 29 , 30 ] demonstrated that DDF values for Polish soils, especially AR and LV profiles, are lower than default FOCUS values. The DDF values for bentazone in subsoil samples from a depth of 40–50, 60–70, and 70–80 cm, were calculated at 0.31, 0.18, and 0.11, respectively, based on the work of Rodríguez Cruz et al [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations